SARS-CoV-2 infections in pediatric and young adult recipients of chimeric antigen receptor T-cell therapy: an international registry report - Hongyan Liu; Colleen Callahan; Shannon L Maude; Kevin Owen McNerney; Rebecca M Richards; Paibel Aguayo-Hiraldo; Friso G Calkoen; Julie-An Talano; Amy Moskop; Adriana Balduzzi; Jennifer Krajewski; Hema Dave; et al. (Journal for ImmunoTherapy of Cancer)
Background Immunocompromised patients are at increased risk of SARS-CoV-2 infections. Patients undergoing chimeric antigen receptor (CAR) T-cell therapy for relapsed/refractory B-cell malignancies are uniquely immunosuppressed due to CAR T-mediated B-cell aplasia (BCA). While SARS-CoV-2 mortality rates of 33%–40% are reported in adult CAR T-cell recipients, outcomes in pediatric and young adult CAR T-cell recipients are limited.Methods We created an international retrospective registry of CAR T recipients aged 0–30 years infected with SARS-CoV-2 within 2 months prior to or any time after CAR T infusion. SARS-CoV-2-associated illness was graded as asymptomatic, mild, moderate, or severe COVID-19, or multisystem inflammatory syndrome in children (MIS-C). To assess for risk factors associated with significant SARS-CoV-2 infections (infections requiring hospital admission for respiratory distress or supplemental oxygen), univariate and multivariable regression analyses were performed.Results Nine centers contributed 78 infections in 75 patients. Of 70 SARS-CoV-2 infections occurring after CAR T infusion, 13 (18.6%) were classified as asymptomatic, 37 (52.9%) mild, 11 (15.7%) moderate, and 6 (8.6%) severe COVID-19. Three (4.3%) were classified as MIS-C. BCA was not significantly associated with infection severity. Prior to the emergence of the Omicron variant, of 47 infections, 19 (40.4%) resulted in hospital admission and 7 (14.9%) required intensive care, while after the emergence of the Omicron variant, of 23 infections, only 1 (4.3%) required admission and the remaining 22 (95.7%) had asymptomatic or mild COVID-19. Death occurred in 3 of 70 (4.3%); each death involved coinfection or life-threatening condition. In a multivariable model, factors associated with significant SARS-CoV-2 infection included having two or more comorbidities (OR 7.73, CI 1.05 to 74.8, p=0.048) and age ≥18 years (OR 9.51, CI 1.90 to 82.2, p=0.014). In the eight patients infected with SARS-CoV-2 before CAR T, half of these patients had their CAR T infusion delayed by 15–30 days.Conclusions In a large international cohort of pediatric and young adult CAR-T recipients, SARS-CoV-2 infections resulted in frequent hospital and intensive care unit admissions and were associated with mortality in 4.3%. Patients with two or more comorbidities or aged ≥18 years were more likely to experience significant illness. Suspected Omicron infections were associated with milder disease.